(untitled) (Journal of the College of Basic Education, 2022)
The educational discourse in the child’s theater is the active act in the education process, providing the information drawn and the mentality of those ages that are palatable and accept the moral, health and psychological discourse in easy and simple ways in terms of artistic language, which can have future and societal constructive dimensions. Discourse education is an important aspect as it is one of the topics Contributing to the creation of a healthy, healthy generation, and based on that necessity, this research included a set of topics related to the educational discourse in the texts of the Iraqi child’s theater, as the first chapter included the methodological framework for the research, represented by the problem, importance and aim of the research in revealing the educational discourse